Lactococcus lactis subsp. cremoris strain JFR1 attenuates Salmonella adhesion to human intestinal cells in vitro. (December 2016) - Zhang, Justina Su; Guri, Anilda; Corredig, Milena; Morales-Rayas, Rocio; Hassan, Ashraf; Griffiths, Mansel; LaPointe, Gisèle
Abstract: Lactococcus lactis subsp. cremoris JFR1 has been studied in reduced fat cheese due to its ability to produce exopolysaccharides (EPS) in situ, contributing to improved textural and organoleptic properties. In this study, the effect of strain JFR1 on virulence gene expression and attachment of Salmonella to HT-29 human colon carcinoma cells was investigated. Overnight cultures of L. lactis subsp. cremoris JFR1 containing EPS, grown in M17 media with 0.5% glucose supplementation, decreased attachment as well as down regulated virulence gene expression in Salmonella enterica subsp. enterica when tested on HT-29 cells. However, EPS isolated from milk fermented with L. lactis subsp. cremoris JFR1 did not affect Salmonella virulence gene expression or attachment to HT-29 cells. These results suggest that EPS does not contribute to the attachment of Salmonella to human intestinal cells. However, the possibility that the isolation process may have affected the structural features of EPS cannot be ruled out. Graphical abstract: Highlights: Lactococcus lactis subsp. cremoris JFR1 reduces Salmonella virulence gene expression. Overnight cultures reduced Salmonella typhimurium attachment to intestinal cells. EPS isolated from fermented milk did not affect gene expression or attachment.